The Implementation of Group Counseling using the Reframing Technique to Reduce Bullying Behavior Tendencies among Madrasah Tsanawiyah Negeri Students - Ramli, Nurul Anisah Fadhilah; Pandang, Abdullah; Aswar, Aswar (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to examine the effectiveness of the reframing technique in reducing bullying tendencies among students at MTsN 1 Makassar City. This research employed a quantitative approach with a quasi-experimental design. The study population consisted of 25 students identified as having bullying tendencies, with a sample of 16 students selected through proportional random sampling. Data were collected through observation and a bullying tendency scale and analyzed using the independent sample t-test. The results indicated that the reframing technique in group counseling services significantly reduced students’ bullying tendencies. The study concludes that the reframing technique is effective as an intervention to decrease bullying behavior in the school environment. The implications of these findings provide a foundation for school counselors and educators to design guidance programs and psychological interventions to prevent bullying behavior among students.